Organizational Best Practices Supporting Mental Health in the Workplace. Issue 12 (6th December 2021) - Wu, Ashley; Roemer, Enid Chung; Kent, Karen B.; Ballard, David W.; Goetzel, Ron Z.
Abstract : Objective: To provide a narrative review of best and promising practices for achieving exemplary mental health in the workplace as the foundation for the inaugural Carolyn C. Mattingly Award for Mental Health in the Workplace. Methods: Research was drawn from peer-reviewed articles using the search terms associated with workplace mental health. Results: Eight categories of best practices were identified: (1) culture, (2) robust mental health benefits, (3) mental health resources, (4) workplace policies and practices, (5) healthy work environment, (6) leadership support, (7) outcomes measurement, and (8) innovation. Conclusion: The review provided the scientific backing to support criteria developed for the Carolyn C. Mattingly Award for Mental Health in the Workplace . By recognizing organizations that apply evidence-based practices in their health and well-being programs, the Mattingly Award may inspire employers to adopt best practices.